Gum mediated synthesis and characterization of CuO nanoparticles towards infectious disease-causing antimicrobial resistance microbial pathogens. Issue 12 (December 2021) - Nithiyavathi, R.; John Sundaram, S.; Theophil Anand, G.; Raj Kumar, D.; Dhayal Raj, A.; Al Farraj, Dunia A.; Aljowaie, Reem M.; AbdelGawwad, Mohamed Ragab; Samson, Y.; Kaviyarasu, K.
Abstract: Background: In this work biologically active CuO nanoparticle were discussed. The literature suggests that CuO shows very good antibacterial activity on both Gram positive and Gram-negative bacterial strains. Further, it is used in antibacterial coatings on various substrates to prevent various kinds of medical equipment's. Here CuO NPs was prepared via greener approach and almond gum is used as a reducing agent. Almond gum is nontoxic and contains huge amount of polysaccharides. Hence, the gum mediated CuO NPs can be used to treat urinary tract infection (UTI). Method: The CuO NPs were characterized using UV, FTIR, XRD and HESEM with EDX analysis. The antibacterial (both Gram positive and Gram negative) effects of CuO NPs were determined with agar well diffusion method. Results: The CuO NPs were characterized by X-ray diffraction pattern result indicates that the monoclinic structure with average crystallite size about 12.91 nm. Straight line model in Scherrer method results found to be crystallite size. The crystallite size and microstrain were estimated in W–H analysis. Lorentz polarization factor, size-strain plot (SSP), morphological index (M-I) and dislocation density were calculated based on x-ray diffraction data. The FTIR analysis confirms presence of Cu and O band. From the absorption spectrum of CuO NPs, it was found to be cutoff wavelength of 230 nm and direct bandgap was found to be 4.97 eV. Morphology analysis shows that the synthesized of CuO NPs reveals agglomerated and spherical in shape. It was found to be 16 nm–25 nm. Energy dispersive spectroscopy (EDX) result indicates percentages of Cu and O element present in the sample. Antimicrobial studies reveal zone of inhibition of CuO NPs. This was used in different pathogens such as gram-positive and Gram-negative bacteria. This study shows exhibit excellent antimicrobial effects of CuO NPs. Conclusion: Hence, in this article the novel and cost-effective method to prepare CuO NPs was discussed. The prepared CuO NPs can be used as an antifungal and antibacterial reagent.